2010
DOI: 10.1029/2009ja014604
|View full text |Cite
|
Sign up to set email alerts
|

Pickup hydrogen distributions in the solar wind at ∼11 AU: Do we understand pickup ions in the outer heliosphere?

Abstract: [1] This study examines the detailed distribution of interstellar pickup hydrogen ions measured by the Surface Wave Process Program instrument on the New Horizons spacecraft en route to Pluto. The observations cover an 8 h interval on 15 October 2008 when the craft was at ∼11.3 AU, constituting the first detailed pickup ion measurements in the outer heliosphere, beyond ∼8 AU. We show the pickup ion cutoff to be roughly twice the solar wind speed, as expected; however, we also measure both a significant suprath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…Since anisotropic PUI models predict more PUIs at low E/q, the measured spectrum of PUIs would appear as though they are anisotropic if the standard constant G is used. This is the reason McComas et al (2010) initially reported a large PUI anisotropy, comparable to that found by Gloeckler et al (1995).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Since anisotropic PUI models predict more PUIs at low E/q, the measured spectrum of PUIs would appear as though they are anisotropic if the standard constant G is used. This is the reason McComas et al (2010) initially reported a large PUI anisotropy, comparable to that found by Gloeckler et al (1995).…”
Section: Discussionsupporting
confidence: 54%
“…The values of μ and ν E are consistent with predictions of these parameters around solar minimum (Ruciński & Bzowski 1995) and consistent with the fact that the measurements were taken during the last extended solar minimum (McComas et al 2008b). The interstellar gas parameters (N, U, and T) were taken from McComas et al (2010) to allow for a direct comparison with their model. We note that these parameters and their uncertainties have just been revised based on new observations from the Interstellar Boundary Explorer (see McComas 2012 and references therein).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5, our results from Fig. 4 (here for 11 AU) are (after an arbitrary shift corresponding to a normalization constant) overplotted (as the black dotted line) on the figure published by McComas et al (2010). Evidently, the step feature can clearly be identified in these data.…”
Section: Numerical Simulationmentioning
confidence: 55%